Rapid elimination of cervical cancer while maintaining the harms and benefits ratio of cervical cancer screening: a modelling study - Jansen, Erik; de Kok, Inge M. C. M.; Kaljouw, Sylvia; Demirel, Erhan; de Koning, Harry J.; Hontelez, Jan (BMC medicine, 2022)
Human papillomavirus (HPV) vaccination and intensifying screening expedite cervical cancer (CC) elimination, yet also deteriorate the balance between harms and benefits of screening. We aimed to find screening strategies that eliminate CC rapidly but maintain an acceptable harms-benefits ratio of screening.
Gesehen am 24.01.2023